Nanocrystalline and stacking-disordered β-cristobalite AlPO4: the now deciphered main constituent of a municipal sewage sludge ash from a full-scale incineration facility. (16th April 2015) - Peplinski, B.; Adam, C.; Adamczyk, B.; Müller, R.; Michaelis, M.; Krahl, T.; Emmerling, F.
Abstract : For the first time evidence is provided that a nanocrystalline and stacking-disordered, chemically stabilized β -cristobalite form of AlPO4 occurs in a sewage sludge ash (SSA). This proof is based on a combined X-ray powder diffraction and X-ray fluorescence investigation of an SSA produced at a large-scale fluidized bed incineration facility serving a catching area with a population of 2 million. The structural and chemical characterization was carried out on 'as received' SSA samples as well as on solid residues remaining after leaching this SSA in sodium hydroxide solution. Thus, it was ascertained that the observed nanocrystalline and stacking-disordered cristobalite-like component belongs to the aluminum phosphate component of this SSA, rather than to its silicon dioxide component. In addition, a direct proof is presented that the chemically stabilized β -cristobalite form of AlPO4 does crystallize from X-ray amorphous precursors under conditions that mimic the huge heating rate and short retention time (just seconds at T ≈ 850°C), typical for fluidized bed incinerators.